MOTIVASI PASIEN DIABETES MELITUS DALAM MENJALANI PROGRAM PENGOBATAN - Muhammad Mudzakkir; Endah Tri Wijayanti; Karisma Azahra Apriyanti (Jurnal EDUNursing, 2026)
Abstract Diabetes mellitus is a chronic disease that requires long-term management through medication adherence, dietary regulation, physical activity, blood glucose monitoring, and lifestyle modification. Motivation is one of the psychological factors that influences patients in maintaining treatment behaviors. This study aimed to describe the level of motivation among patients with diabetes mellitus in undergoing treatment programs at the Outpatient Clinic of Muhammadiyah Ahmad Dahlan Hospital, Kediri. This study employed a quantitative descriptive design with a cross-sectional approach. A total of 41 respondents were selected using purposive sampling. Data were collected using a motivation questionnaire and analyzed using univariate analysis. The results showed that most respondents had a high level of motivation (58.5%), followed by moderate motivation (31.7%) and low motivation (7.3%). The findings indicate that most patients have adequate motivation to maintain treatment adherence and disease management. Nurses are expected to strengthen patient motivation through education, counseling, and family involvement to improve treatment outcomes. Keywords: diabetes mellitus, motivation, treatment, outpatient, nursing